Fire Safety Management Plan Implementation in Heritage Building - Kasim, Narimah; Zainal, Nur Ishmah Hanani; Zainal, Rozlin; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2021)
Heritage building that were constructed before Uniform Building By-Laws (UBBL 1984) were formulated, rise concern in aspect of fire safety management, moreover when the management are still in poor condition seeing some building such as Fort Renee, Kuching, Sarawak involved in fire accident. Therefore, the purpose of the study was to examine current practices, challenges and ways to improve fire safety management plan implementation in heritage building. This study adopted qualitative method by conducting interview to the museum management division under Melaka Museums Corporation (PERZIM) for the selected heritage building which is Museum Stadhuys Complex. All data from the interviews were distributed by using virtual method, which are Mobile phone, Email and Whatsapp. The data collections were transcribed using Microsoft Word software. This research discovered the current practices used in the heritage building by PERZIM Safety and Health Committee (JKKP) carried out fire safety risk assessment and fire safety management plan in aspect of emergency planning, emergency action and maintenance. Also, the main challenge in conducting the fire safety management plan was the cost of the fire safety equipment’s maintenance. Meanwhile, few ways to improve the fire safety management plan were make basic fire safety training more effective and spread more awareness on fire safety awareness among the building occupants. Through this study, it is hoped to provide useful and beneficial relevant information on fire safety management plan to the related parties and building that have poor fire safety management plan implementation.